Activation and Contraction of Human “Vascular” Smooth Muscle Cells Grown From Circulating Blood Progenitors - Ahmetaj-Shala, Blerina; Marei, Isra; Kawai, Ryota; Rothery, Stephen; Pericleous, Charis; Mohamed, Nura A.; Gashaw, Hime; Bokea, Kalliopi; Samuel, Jake; Vandenheste, Annabelle; Shala, Fisnik; Kirkby, Nicholas S.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Blood outgrowth smooth muscle cells (BO-SMCs) offer the means to study vascular cells without the requirement for surgery providing opportunities for drug discovery, tissue engineering, and personalized medicine. However, little is known about these cells which meant that their therapeutic potential remains unexplored. Our objective was to investigate for the first time the ability of BO-SMCs and vessel-derived smooth muscle cells to sense the thromboxane mimetic U46619 by measuring intracellular calcium elevation and contraction. U46619 (10–6 M) increased cytosolic calcium in BO-SMCs and vascular smooth muscle cells (VSMCs) but not in fibroblasts. Increased calcium signal peaked between 10 and 20 s after U46619 in both smooth muscle cell types. Importantly, U46619 (10–9 to 10–6 M) induced concentration-dependent contractions of both BO-SMCs and VSMCs but not in fibroblasts. In summary, we show that functional responses of BO-SMCs are in line with VSMCs providing critical evidence of their application in biomedical research.